PROSES KOMUNIKASI INTERNAL KRISNA OLEH-OLEH DALAM PENYULUHAN PROTOKOL KESEHATAN COVID-19 - Widhiastawa, I Made Krishna; Pamungkas, Indra Novianto Adibayu (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
During the pandemic, it is necessary to implement a new order of life, especially in the tourism business, health protocols are a way to prevent the spread of Covid-19. This study was conducted to determine The Process Of Internal Communication Krisna Oleh-Oleh In Countering Protocol Health Covid-19, seen from the theory of the Communication Process of Effendy, Onong Uchjana which consists of Sender, Encoding, Message, Media, Decoding, Receiver, Response, Feedback, Noise. This research was conducted using a descriptive qualitative method by conducting interviews with the Owner, Manager and Staff of Krisna Oleh-Oleh. In addition, the researchers also carried out direct observations of the condition of Krishna Oleh-Oleh. The findings of this study are the communication process carried out by Krisna Oleh-Oleh using the communication strata of High, Middle, Low Management effectively to convey messages. The findings of the second researchers found that direct health protocol counseling was very effectively received by Krisna Oleh-Oleh employees. The conclusion of this study is that Krisna Oleh-Oleh is optimal enough in communicating health protocols directly to internally Krisna Oleh-Oleh. However, there are several things that must be paid more attention to, such as the coordination carried out in providing health protocol information, and also the need for special monitoring of health protocols carried out internally by Krisna Oleh-Oleh.